ENCOURAGING COLLABORATION BETWEEN STEM EDUCATORS,LANGUAGE ARTS TEACHERS, AND SOCIAL SCIENCE INSTRUCTORS TO DEVELOP COMPREHENSIVE DIGITAL LITERACY PROGRAMS - Rerin Maulinda; Alim Hardiansyah; Loso Judijanto; Mohammad Ahmad Bani Amer; Iyad Abdallah Al- Shreifeen (International Journal of Teaching and Learning, 2023)
This study advocates for the collaborative efforts of STEM educators, language arts teachers, and social science instructors in crafting holistic digital literacy programs. Recognizing the interdisciplinary nature of digital literacy, the collaboration seeks to integrate technical skills with critical thinking, communication, and information evaluation. By leveraging the expertise of educators from diverse domains, the proposed programs aim to foster a comprehensive set of digital competencies essential for navigating the complexities of the digital age. Through collaborative curriculum design and joint instructional strategies, students stand to benefit from a cohesive and well- rounded digital literacy education. This interdisciplinary approach enhances students' technological proficiency and cultivates the analytical and communicative skills necessary for informed digital citizenship. The study advocates for a paradigm shift in educational collaboration, emphasizing the collective responsibility of educators across disciplines in preparing students for success in an increasingly digitalized society.